2018
DOI: 10.1111/ajt.14492
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported health outcomes in long-term lung transplantation survivors: A prospective cohort study

Abstract: During the last three decades lung transplantation (LTx) has become a proven modality for increasing both survival and health‐related quality of life (HRQoL) in patients with various end‐stage lung diseases. Most previous studies have reported improved HRQoL shortly after LTx. With regard to long‐term effects on HRQoL, however, the evidence is less solid. This prospective cohort study was started with 828 patients who were on the waiting list for LTx. Then, in a longitudinal follow‐up, 370 post‐LTx patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…Several prospective studies have shown that QoL after lung transplantation improves significantly . In accordance with this previous research, we could demonstrate that QoL increased significantly in the first 3 months after the transplantation and remained stable in following the 3 months.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several prospective studies have shown that QoL after lung transplantation improves significantly . In accordance with this previous research, we could demonstrate that QoL increased significantly in the first 3 months after the transplantation and remained stable in following the 3 months.…”
Section: Discussionsupporting
confidence: 91%
“…Prospective long‐term studies provide evidence that quality of life (QoL) after lung transplantation improves significantly and remains stable over a period until 15 years . According to recent studies, higher levels of post‐transplant depression and distress increase the risk for long‐term transplant‐related morbidity and mortality; thus, the psychological processes following transplantation may be crucial for the subsequent somatic outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Before transplantation, a patient’s HRQoL is significantly reduced due to clinical dysfunction of the failing organ and psychosocial distress. Shortly after transplantation, a significant increase in HRQoL is observed [ 11 , 12 ]. However, life-long, immunosuppressive regimens are necessary to prevent organ rejection, and chronic exposure to these medications is associated with complications that adversely affect the HRQoL of solid organ transplant recipients [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing health‐related quality of life (HRQL), and other related health domains, has become an important tool in evaluating the outcomes of solid organ transplantation as evidence suggests transplant provides both HRQL and survival benefits 1–4 . Understanding HRQL is particularly important in organs, like the lung, where the survival benefit is more limited as compared to other solid organs.…”
mentioning
confidence: 99%
“…In lung transplantation, single‐ and multicenter studies have reported patient‐perceived improvements in physical and mental domains across different HRQL instruments after transplantation 1–4 . However many of these studies are not recent and may not reflect modern practices, and have been limited by cross‐sectional design, and survivor bias 5,6 .…”
mentioning
confidence: 99%